The challenge of hunger: The 2008 Global Hunger Index [issue brief] - von Grebmer, Klaus; Fritschel, Heidi; Nestorova, Bella; Olofinbiyi, Tolulope; Pandya-Lorch, Rajul; Yohannes, Yisehac (International Food Policy Research Institute, 2008)
With high food prices threatening the food security of millions of vulnerable households around the world, hunger and malnutrition are back in the headlines. The world is making only slow progress in reducing food insecurity, according to the Global Hunger Index (GHI). Some regions—in particular South and Southeast Asia, the Near East and North Africa, and Latin America and the Caribbean—have made significant headway in combating hunger and malnutrition since 1990, but in South Asia and Sub-Saharan Africa, the GHI remains high. Moreover, progress in Sub-Saharan Africa since 1990 has been marginal. The GHI is a tool developed by IFPRI for regularly tracking the state of global hunger and malnutrition. This year’s index reflects data until 2006—the most recent available global data—and does not yet take account of the latest changes in the world food system, in which a number of factors are converging to raise prices for agricultural commodities to their highest levels in decades. Food prices appear likely to remain high in the near term, leading to food and nutrition insecurity for poor people around the globe. In this risky and changing environment, the GHI highlights key trends and the geographic areas of greatest vulnerability.